Leadership secrets of Saint Paul. - Caliguire, Jeff. (Manila, Philippines : Lighthouse Books, 2003)
1. Leadership.--Religious aspects.--Christianity. 2. Paul. The Apostle. Saint.
Faculty
Keywords: Paul, -- the Apostle, Saint; Leadership -- Religious aspects -- Christianity